Orchard and bin treatment with entomopathogenic nematodes (Rhabditida: Steinernematidae and Heterorhabditidae) for the control of the codling moth (Cydia pomonella) - Odendaal, Deidre (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.